Evaluation of color matching of three single-shade composites employing simulated 3D printed cavities with different thicknesses using CIELAB and CIEDE2000 color difference formulae - Kariper Engin; Cilingir Aylin (Reviews on Advanced Materials Science)
This study assessed the color-matching capability of three single-shade composites that employ simulated resin 3D-printed cavities with different cavity depths using CIELAB and CIEDE2000 formulas. A cylindrical model with standardized cavities was generated. One hundred and fifty blank specimens were fabricated and divided into three groups (n = 50) and then into five subgroups. The five subgroups included four groups of specimens with 0.5, 1, 2, and 4 mm cavities and a control group of specimens without cavities (n = 10). Cavities were filled with Vittra Unique (VU), Omnichroma (OC), and OptiShade (OS). Color measurements were done using a clinical spectrophotometer. The color differences for all composites were calculated as ΔE and ΔE 00 using CIELAB coordinates. The color parameter data were analyzed (α = 0.05). OS had significantly lower ∆E and ∆E 00 values than the other composites for all layer thicknesses (p < 0.05). VU, OC, and OS had the lowest ∆E and ∆E 00 values at 0.5 mm (p < 0.05). Color matching of monochromatic composites decreased as the layer thickness increased. OS achieved the best color matching in this study. Single-shade composites are important for reducing chairside time and gaining confidence in clinical practice. CIELAB and CIEDE2000 color difference formulae can be used in different studies with similar results.